Roman dogs from the Iberian Peninsula and the Maghreb – A glimpse into their morphology and genetics. (25th March 2018) - Pires, Ana Elisabete; Detry, Cleia; Fernandez-Rodriguez, Carlos; Valenzuela-Lamas, Silvia; Arruda, Ana Margarida; De Grossi Mazzorin, Jacopo; Ollivier, Morgane; Hänni, Catherine; Simões, Fernanda; Ginja, Catarina
Abstract: In this study, we integrate osteometric and palaeogenetic data to investigate dog variability in the Roman Empire in Iberia and North Africa. Osteometry was used to distinguish the status—domestic or wild, of approximately 2000 years old Canis remains and to understand to what extent teeth and long bones varied in dogs in the Roman provinces of Mauretania Tingitana, Lusitania and Tarraconensis . High-throughput 454-DNA sequencing technology was used to obtain mitochondrial DNA (mtDNA) sequences from 15 bone and teeth samples. We identified five dog haplotypes from partial sequences of the hypervariable D-loop region. MtDNA haplotypes were grouped into two of the four major clades found in present-day dogs. We detected three clade A haplotypes in 12 samples from Portugal, Spain and Morocco, and a single clade D haplotype in 3 samples from Spain. So far, this is the oldest evidence for the presence of dog clade D in Iberia. It is dated to the late Roman occupation in the 4th-5th cent. AD ( ca. 1, 600 years ago). Our results confirm the existence of distinct dog morphotypes in Roman times that also harboured distinct genetic lineages. According to our data, dogs from distinct mtDNA lineages (clades A and D) have been continuously bred in the Iberian Peninsula since at least 1600 years ago. Moreover, the sharing of matrilines between dogs from Spain and North Africa may indicate gene flow. Dogs could have been easily transported between these regions by humans along maritime and terrestrial trade routes. These results provide new insights into pre-Roman and Roman domestication practices, confirming selection practices were extensively applied to dogs during the first centuries of our era in the Iberian Peninsula. We show that the greater size variability of teeth length (and consequently cranium) and long bone breadths (and consequently phenotype) of Roman dogs in the Iberian Peninsula, is concomitant with the detection of diverse and rare maternal lineages. This would reflect an intensification of dog breeding and the use of non-local dogs for breeding.